The skeletal-related events of denosumab versus zoledronic acid in patients with bone metastases: A meta-analysis of randomized controlled trials - Zhicai Zhang; Feifei Pu; Zengwu Shao (Journal of Bone Oncology, 2017)
Objective: The meta-analysis was used to evaluate the skeletal-related events (SREs) and efficacy of denosumab versus zoledronic acid (ZA) in patients with bone metastases. Methods: The data of this meta-analysis study were searched from PUBMED, EMBASE, Cochrane Library, Web of Science with Conference Proceedings, Elsevier and China National Knowledge Infrastructure (CNKI) databases till August 2017. Two independent reviewers reviewed the reference lists of relevant articles. The fixed-effects model and random-effects model were used to summarize relative estimates and 95% confidence intervals (CIs) according to the heterogeneity of the included studies. Results: Three randomized controlled trials (RCTs) including 4050 patients were identified in this meta-analysis study. The pooled analysis showed that denosumab could significantly reduce SREs, series SREs [Odds Ratio (OR) = 0.84; 95% CI, 0.74â0.95, I2 = 0%, P = 0.008] in patients with bone metastases as compared with ZA. Similar results of spinal cord compression SRE and surgery to bone SRE were obtained with (OR = 0.84; 95% CI, 0.70â1.01, I2 = 0%, P = 0.07) and (OR = 0.92; 95% CI, 0.78â1.08, I2 = 0%, P = 0.28) separately, radiation to bone SRE (OR = 0.72; 95% CI, 0.46â1.10, I2 = 11%, P = 0.13) and pathological fracture SRE (OR = 0.78; 95% CI, 0.35â1.73, I2 = 25%, P = 0.54) showed similar results, there were no significant difference between denosumab and ZA in patients with bone metastases. Conclusion: Denosumab was more effective than ZA in reducing the incidence of SRE in patients with bone metastases. Keywords: Skeletal-related event, Denosumab, Zoledronic acid, Bone metastases, Meta- analysis